Relationship between steroid hormones and metabolic profile in women with polycystic ovary syndrome - Lazúrová, I; Lazúrová, Z; Figurová, J; Ujházi, S; Dravecká, I; Mašlanková, J; Mareková, M (Physiological research, 2019)
Polycystic ovary syndrome (PCOS) is commonly associated with a higher cardiometabolic risk. The relationship between steroid hormones and cardiometabolic profile in PCOS has been evaluated, but no single hormonal predictor of this association has been identified to determine. To determine the relationship between steroid hormones and cardiometabolic risk factors in PCOS women. Study included 64 women diagnosed with PCOS. Fasting blood samples were analyzed for biochemical, metabolic parameters and sex steroid hormones. PCOS women with BMI>/-27 had significantly higher serum free testosterone (FT), free androgen index (FAI), estrone (E1) (p=0.014, p=0.02, p=0.01) than those with normal weight. In all subjects E1 positively correlated with BMI (p=0.0067), serum insulin (p=0.0046), HOMA-IR (p=0.0125) and negatively with HDL-cholesterol (p=0.009). FAI positively correlated with serum cholesterol (p=0.0457), triacylglycerols (TAG) (p=0.0001), HOMA-IR (p=0.037), and glycemia (p=0.0001), negatively with HDL-cholesterol (p=0.029). In multiple linear regression model E1 most significantly predicted HOMA-IR, whereas FT/FAI predicted HDL-cholesterol and BMI. We conclude that PCOS women with marked overweight or obesity have higher FT, FAI and E1 as compared with nonobese PCOS subjects. E1 and FT may predict worse cardiometabolic profile in PCOS.
Keywords: index tělesné hmotnosti; syndrom polycystických ovarií; Obesity; krevní glukóza; metabolom; Polycystic Ovary Syndrome; Adult; mladý dospělý; Body Mass Index; Metabolome; Blood Glucose; Young Adult; ženské pohlaví; pohlavní steroidní hormony; Humans; biologické markery; obezita; Gonadal Steroid Hormones; dospělí; Biomarkers; inzulinová rezistence; Female; Insulin Resistance; lidé